2015
DOI: 10.1016/j.jslw.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Task complexity effects on the complexity and accuracy of writing via text chat

Abstract: Despite limitations with text chat as a mode of writing (e.g., a simplified register, short turns), researchers have argued that it offers unique advantages as a site for language practice. However, realizing these advantages in second language (L2) writing-to-learn environments may depend on whether tasks are implemented in a way that facilitates learners' attention to language form in their writing. It follows that the design and selection of appropriate tasks to use in Computer-Mediated Communication (CMC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 58 publications
1
14
0
2
Order By: Relevance
“…These findings, which are similar to Nik's (2010) results indicating that simple tasks in SCMC led to improved accuracy, suggest that complex tasks may not facilitate L2 learning in SCMC in the same way that they do in FTF contexts, possibly due to the noncontingency of feedback episodes (Baralt, 2013). Adams, Nik, and Newton (2015) also found that task complexity affected the accuracy but not the complexity of learners' production in SCMC contexts, findings that fail to meet the predictions set forth by the cognition hypothesis (Robinson, 2001). Because much of the research on task complexity is situated within the framework of Robinson's cognition hypothesis, whose central claim is that cognitive complexity should serve as the determining factor for the sequencing of simple and complex tasks, it is necessary to also investigate sequencing in a computer-mediated learning context.…”
Section: Task Complexity and Sequencingsupporting
confidence: 84%
“…These findings, which are similar to Nik's (2010) results indicating that simple tasks in SCMC led to improved accuracy, suggest that complex tasks may not facilitate L2 learning in SCMC in the same way that they do in FTF contexts, possibly due to the noncontingency of feedback episodes (Baralt, 2013). Adams, Nik, and Newton (2015) also found that task complexity affected the accuracy but not the complexity of learners' production in SCMC contexts, findings that fail to meet the predictions set forth by the cognition hypothesis (Robinson, 2001). Because much of the research on task complexity is situated within the framework of Robinson's cognition hypothesis, whose central claim is that cognitive complexity should serve as the determining factor for the sequencing of simple and complex tasks, it is necessary to also investigate sequencing in a computer-mediated learning context.…”
Section: Task Complexity and Sequencingsupporting
confidence: 84%
“…Leki (2009) also claimed that using writing to develop second language may be a central objective in second language learning. This new perspective has been called "writing-to-learn-language (wll)" and emphasizes the role of writing as a medium for language development as has been supported by studies as recent as that of Adams, Alwi, and Newton (2015). There are several traits of writing that have led prominent authors to argue that writing plays an important role in language learning.…”
Section: Writing Skillsmentioning
confidence: 99%
“…With CMC, the affordances of online planning are greatly expanded. While the synchronous nature of CMC bestows upon the writing process in text chat characteristics of speaking such as the possibility for overlapping turns, it is not a simple hybrid of both production modes (Adams, Alwi, & Newton, 2015). Compared to speaking, CMC allows for a greater amount of lag time between turns, which can be utilized for online planning (Sauro & Smith, 2010).…”
Section: Second and Foreign Language Writing And Computer-mediated Comentioning
confidence: 99%